Girls can do anything - Hart, Caryl; Pye, Ali (Scholostic : Barron's, 2018)
"[This book is] all about the things girls can do. Whether she dreams of being a vet that heals people's pets, a firefighter that braves the flames, an astronaut floating in deep, dark space, or a fearless jungle explorer, [this book stresses] there's nothing that a girl can't do"--Provided by publisher.
Kirkus Review
Kirkus Review, July 2018
2.2
K-3.
K-3
Keywords: Girls -- Juvenile literature; Occupations -- Juvenile literature; Self-confidence -- Juvenile literature; Sex role -- Juvenile literature; Girls; Occupations; Self-confidence.; Sex role; Gender role; Girls; Occupations; Self-confidence.; Illustrated works